Scooby-Doo! and the fishy phantom - McCann, Jesse Leon (New York : Scholastic, 2012)
When Velma and the gang get a sneak peek of the rare Rainbow Flounder during an after-hours tour at the Coolsville Aquarium, a Fishy Phantom shows up and steals the exhibit.
Reprint. Originally published: 2006.
Keywords: Fishes -- Fiction; Aquariums -- Fiction; Robbers and outlaws -- Fiction; Dogs -- Fiction; Mystery and detective stories; Fishes -- Fiction; Aquariums -- Fiction; Thieves -- Fiction; Dogs -- Fiction; Mystery fiction